Elucidating the Impact of Cobalt Doping on the Lithium Storage Mechanism in Conversion/Alloying‐Type Zinc Oxide Anodes. Issue 9 (17th June 2016) - Mueller, Franziska; Geiger, Dorin; Kaiser, Ute; Passerini, Stefano; Bresser, Dominic
Abstract: Herein, an in‐depth investigation of the influence of transition‐metal doping on the structural and electrochemical characteristics of a hybrid conversion/alloying‐type lithium‐ion anode material is presented. Therefore, pure zinc oxide (ZnO) and cobalt‐doped ZnO (Zn0.9 Co0.1 O) were investigated comparatively. Characterization by using X‐ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM) confirmed the successful incorporation of the cobalt (Co) dopant into the wurtzite ZnO structure, which led to a decreased particle size for the doped compound. The in situ electrochemical XRD analysis of the first de‐/lithiation of ZnO and Zn0.9 Co0.1 O revealed the highly beneficial impact of the transition‐metal dopant on the reversible degradation of lithium oxide (Li2 O) and suppression of zinc crystallite growth upon lithiation; both effects are essential for greatly improved electrochemical performance. As a result, Co doping leads to a substantially increased specific capacity from 326 mAh g −1 for pure ZnO to 789 mAh g −1 for Zn0.9 Co0.1 O after 75 full charge–discharge cycles. Abstract : Reversible conversion : The introduction of Co into the ZnO wurtzite structure results in a two‐ to threefold enhanced specific capacity by inhibiting zinc crystal growth upon (de)lithiation, which thus enables long‐term reversible cycling of hybrid conversion/alloying‐type lithium‐ion anodes.